Educational judicial treatment of bullying in children under 18 years of age - Lorenzo, Susana Tamayo (Avances en Supervisión Educativa, 2021)
Bullying produces effective harm that no one has a duty to bear. The article focuses on children under 18 years of age precisely because they are people in a period of development, hence their vulnerability. The methodology used has been fundamentally the bibliographic analysis. It has started from the state of affairs, analyzing how it has gone unnoticed, it has been externalized until protection against violence is configured as a right of children. Intervening in time is essential to resolve the conflict and avoid the establishment of violent roles that may continue to worsen in the future.